A reliable integrative autocorrelator device for particle fluctuation rate monitoring. (November 2017) - Pan, Boan; Li, Ting; Li, Yan; Xu, Guoyi
Abstract: The monitoring of particle fluctuation rate is of great importance in the biomedical field, especially in applications concerning the near-infrared spectroscopy (NIRS) monitoring of blood flow. Blood flow is one of the most important indexes to estimate the body functional status, while the existing technologies for its measurements have some limitations. NIRS is non-invasive, continuous real-time, applicable to blood flow monitoring of a variety of vessel sizes and deeper depths. Autocorrelation module, which is capable of processing optical signals and getting blood flow data with the upper computer module, is an important part of near-infrared monitoring blood flow method. In this study, we integrated the upper computer module into the autocorrelator device, reduced man-made errors caused by multiple modules, and made the device more convenient and reliable. We also tested its performance and reliability. The result showed that the device has great potentiality in measuring the particle fluctuation rate conveniently, accurately and reliably. In future, the device will be tested in noninvasive clinic trials to verify its monitoring effects. Highlights: Innovatively developed reliable integrative autocorrelator device. Adding the pseudo random number generator and the data calibrator to ensure the robustness and stability of the device. A series of experiments conducted to verify the Robustness and stability of this device.